Evaluation of anti-oxidant activity of Teneligliptin by DPPH assay- an In-Vitro study - Dr.S.SHARANYA; Dr.P.ELANGO; Dr.DARLING CHELLATHAI DAVID (International Journal of Pharma and Bio Sciences, 2017)
To assess the antioxidant potential of the new anti-diabetic drug Teneligliptin using DPPH assay. DPPH radical scavenging activity was done using the method of NazninAraandHasanNur (2009)- . Here butylated hydroxy toluene (BHT) was used as the standard compound in this study.The free radical scavenging property of Teneligliptin was found to be 71.87± 0.12% , 65.62± 0.25% , 60.10± 0.33% , %inhibition while that of BHT was found to be 93.91±0.76%, 82.4 ± 0.34 , 74.12± 0.16% , % inhibition at the following concentrations 1000, 750, 500 μg/ ml respectively.From the study, it was found that the study drug teneligliptin has good antioxidant property which could act as a cytoprotective agent in conditions associated with oxidative stress along with its anti-diabetic action.